Kajian Literatur : Hubungan Pengetahuan dan Sikap terhadap Penanganan Nyeri Haid (Dismenore) di Kalangan Remaja Putri - Muthi’ah Irta Zhafirah; Femmy Andrifianie (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Dysmenorrhea or menstrual pain, is a common health issue among adolescent girls, often disrupting daily activities and quality of life. Effective management of dysmenorrhea is strongly influenced by the level of knowledge and attitudes of adolescent girls toward this condition. This literature review aims to analyze the relationship between knowledge and attitudes regarding the management of menstrual pain among adolescent girls. Various studies indicate that while adequate knowledge about dysmenorrhea is important, the correlation between knowledge and attitude is not always significant. Some research finds that good knowledge does not necessarily translate into a positive attitude towards pain management, as other factors such as stress, anxiety, and reluctance to take action also play a role. However, there are studies that show a positive relationship between increased knowledge and better attitudes toward dysmenorrhea management, although the strength of this association is very weak. Most adolescents tend to choose non-pharmacological management, such as rest and warm compresses, but many still ignore menstrual pain due to a lack of knowledge and information. Therefore, educational interventions and counseling in schools are essential to improve knowledge and foster positive attitudes in managing dysmenorrhea among adolescent girls. These efforts are expected to help adolescent girls manage menstrual pain more effectively and enhance their quality of life.